Freshwater cyanoprokaryota blooms in the Swan Coastal Plain wetlands: ecology, taxonomy and toxicology - Kemp, Annabeth S. (Curtin University, 2009)
Relatively little published information on cyanoprokaryote (blue-green algal) blooms in the freshwater wetlands in Western Australia is available. There has been little research on the urban lakes and rivers, examining the relationship between environmental conditions and toxin-producing blooms. In this project the ecology, morphology and toxicity of cyanoprokaryota blooms in 27 metropolitan lakes and sumplands, as well as three major rivers, from 2000 to 2003, on the Swan Coastal Plain (SCP) in the southwest of Western Australia were investigated.A total of 24 species were identified and described, of which nine species had not been previously documented in the area. This included the potentially toxic species Cylindrospermopsis raciborskii, Aphanizomenon ovalisporum and Anabaena bergii var. limnetica. An illustrated guide to the common bloom-forming species was generated using conventional taxonomic criteria.Microcystis flos-aquae and Microcystis aeruginosa were the dominant bloom-forming cyanoprokaryotes, widespread in their distribution. Anabaena circinalis, A. bergii var. limnetica and Anabaenopsis elenkinii were the common filamentous species. Anabaena circinalis was common to certain freshwater sites, while A. bergii var. limnetica and A. elenkinii occurred in salinity ranging from fresh (< 1ppt) to hyposaline (3-10 ppt). Sites with similar species assemblages were identified using two-way indicator species analysis and clustering analysis. From this, a distinct distribution pattern emerged, which was defined by the main genera observed in the lakes – Microcystis, Anabaena, Aphanizomenon and Anabaenopsis.The spatial and temporal distribution of the common bloom-forming cyanoprokaryote species was examined in conjunction with spring-summer physico-chemical data using principal component analysis. It was found that pH, water temperature and electrical conductivity/salinity accounted for variations among the lakes, with electrical conductivity the variable explaining the greatest variation. Lakes located on the coast, or further inland at the base of the Darling Scarp, were more hyposaline to saline, and the remaining lakes were fresh. Although the SCP lakes form consanguineous groups based on geochemistry and hydrology, no similarities among them were found in terms of water quality.The relationship between nitrogen (N) and phosphorus (P) concentrations (total and dissolved inorganic) and cyanoprokaryote community structure (N-fixing versus non-N-fixing species) was investigated in five selected lakes; Yangebup Lake, Bibra Lake, Blue Gum Lake, Tomato Lake and Emu Lake. The lakes ranged from mesotrophic to eutrophic and supported spring-summer blooms containing multiple species. Overall an inverse relationship between cyanoprokaryote abundance and total ambient nutrient concentrations at the time of the blooms was evident. No transition in dominance in the community was observed in Yangebup Lake, Emu Lake and Bibra Lake, as they were dominated by non-heterocytic species (M. aeruginosa and M. flos-aquae) throughout spring and summer. For Yangebup Lake and Bibra Lake, the abundance of non-heterocytic species decreased concomitantly with decreasing dissolved inorganic N. In contrast, heterocytic species (A. circinalis) dominated the spring community in Tomato Lake, and summer community in Blue Gum Lake, when N and P concentrations were at their highest.The presence of microcystins in Microcystis dominated blooms was examined using high performance chromatography. A total of 32 natural bloom samples, representing 13 lakes, were analysed for microcystin variants; -LR, -RR and -YR. Twenty-eight samples proved to be toxic with the highest total microcystin concentration from 1645 to 8428.6 µg L[superscript]-1, the lowest concentrations were less than 10 µg L[superscript]-1 with some below the detection limit. Microcystis aeruginosa and M. flos-aquae were associated with these microcystin-containing blooms, although M. flos-aquae appear to be less toxic. The presence of Nodularia spumigena in the Lake Yangebup was associated with high concentrations of nodularin (1664 µg L[superscript]-1).Employing enzyme-linked immunosorbent assay for microcystins and the brine shrimp (Artemia) bioassays allowed a greater number of lake samples to be analysed and provided a rapid assessment of toxicity. The three methods for cyanotoxin detection verified Yangebup Lake, Herdsman Lake, Hyde Park, Jackadder Lake and Emu Lake as highly toxic sites. Low toxicity was demonstrated in samples from Lake Goollelal, Lake Joondalup, Lake Claremont, Blue Gum Lake and North Lake. These results provided the first evidence of cyanotoxin producing blooms in urban lakes of the SCP.A comparative study on cyanoprokaryota blooms in Swan River estuary, upper Canning River and upper Serpentine River found that these sites, although hyposaline to saline, contained species that were common in the freshwater lakes. Sampling the river systems showed M. aeruginosa, M. flos-aquae, A. circinalis, A. elenkinii and Planktothrix planctonica to be cosmopolitan in distribution, present in SCP wetlands of varied salinity. Similarities between the upper Canning River and lakes in environmental conditions and species assemblage were demonstrated using multivariate analyses.Toxin analysis of bloom samples from the Swan River and upper Canning River revealed microcystin concentrations were less than that of the surrounding lakes (1.05-124.16 µg L[superscript]-1). Similarly, nodularin concentrations were higher in Yangebup Lake than the upper Serpentine River. However, the dominance of Anabaena in Canning River samples, and the highly toxic result from the Artemia bioassay suggests microcystin is not the predominant cyanotoxin in this wetland.This study has produced an overview of the distribution and morphology of cyanotoxin-producing cyanoprokaryotes in the SCP wetlands. The data presented provide the basis for further cyanoprokaryote research in Western Australia, in particular the molecular characterisation of bloom-forming toxic species.